A Influência do Controle Externo Exercido pelo TCEES na Aplicação dos Recursos Municipais do FUNDEF - Marinot, Marcio Batista (2001)
The Maintenance and Development for the Fundamental Education and Teacher's Appreciation Fund - (FUNDEF), has an accounting nature and its resources in the state of Espírito Santo are managed by the Tribunal de Contas do Estado do Espírito Santo (TCEES), department that supervises the state and cities activities. This work intends to identify how the management done by the TCEES influences in how FUNDEF applies its resources in the cities. The management done by the TCEES through accounting, financial, budgetary, operational and material resourses supervision, is by definition and according to the law, the main element of the right application of the public resources. Nevertheless, it is presumed that these supervision departments are not well prepared to control the aplication of FUNDEF resources. The confrontation of the theory, according to the regulation of the Fund, book research and legislation, including also the practical part that results from the research in the TCEES, can greatly help to control FUNDEF resources.